2008
DOI: 10.1007/s11199-007-9385-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Obligations on Young Women’s Decisions During the Transition to College: A Comparison of Latina, European American, and Asian American Students

Abstract: In this study, we hypothesized that (1) Latina and Asian American undergraduate women would report more frequently fulfilling family obligations than would European Americans, and (2) fulfillment of family obligations would predict students' residential and working plans for their first semester of college. Results of an online survey completed by 296 American first-year students showed that Latinas more frequently fulfilled family obligations than did Asian Americans and European Americans, although fulfillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Most of these studies have argued that such experiences are beneficial for youth in terms of increasing their relationship quality and time spent with families and cognitive and linguistic skills (Chao, 2006;Dorner et al, 2008;McHale, Updegraff, Kim, & Kansler, 2009). However, studies have also found either no associations or associations with negative outcomes like lower school performance and greater stress and adjustment problems (Chao, 2006;Fuligni, Yip, & Tseng, 2002;Sy & Brittain, 2008;Walsh, Shulman, Bar-On, & Tsur, 2006). In one of the few studies conducted outside the United States, Walsh and colleagues found that immigrant youth in Israel from families that were cohesive and supportive of adolescent autonomy tended to experience higher rates of parentification (i.e., youth assuming responsibilities of parents) but also better coping skills than nonimmigrant youth.…”
Section: Family Socialization and Parentingmentioning
confidence: 99%
“…Most of these studies have argued that such experiences are beneficial for youth in terms of increasing their relationship quality and time spent with families and cognitive and linguistic skills (Chao, 2006;Dorner et al, 2008;McHale, Updegraff, Kim, & Kansler, 2009). However, studies have also found either no associations or associations with negative outcomes like lower school performance and greater stress and adjustment problems (Chao, 2006;Fuligni, Yip, & Tseng, 2002;Sy & Brittain, 2008;Walsh, Shulman, Bar-On, & Tsur, 2006). In one of the few studies conducted outside the United States, Walsh and colleagues found that immigrant youth in Israel from families that were cohesive and supportive of adolescent autonomy tended to experience higher rates of parentification (i.e., youth assuming responsibilities of parents) but also better coping skills than nonimmigrant youth.…”
Section: Family Socialization and Parentingmentioning
confidence: 99%
“…Family obligation first emerged as an important construct in research on adult behavior towards aging adults (Stein, 1992); however, research by Fuligni and colleagues (e.g., Fuligni, Tseng & Lam, 1999) has demonstrated its relevance during adolescence and early adulthood, particularly among youth of color. Early research on adolescent family obligation demonstrated group differences by race, ethnicity and immigrant status (e.g., Fuligni et al, 1999; Hughes, 2001), and linked family obligation to educational outcomes (e.g., Fuligni, 2007; Sy & Brittian, 2008) and emotional and behavioral adjustment (e.g., Juang & Cookston, 2009; Yau, Taspoulos-Chan & Smetana, 2009) among diverse youth. More recent studies have extended our understanding of family obligation in two important ways.…”
Section: Introductionmentioning
confidence: 99%
“…Explanations for college access and educational opportunities for Latinas have relied historically on gendered explanations emphasizing marianismo-Latinas' self-sacrificing role, underscoring women's roles inside the home (Sy & Brittian, 2008). This deficit explanation sees…”
Section: Latina Student Mothers In Higher Educationmentioning
confidence: 99%